PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA MODEL INKUIRI TERBIMBING DITUNJANG MEDIA PhET UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA - Yunita Yunita; Sri Poedjiastoeti; Rudiana Agustini (Universitas Negeri Surabaya, 2017)
The purpose of this research is to produce learning materials of science bases on guided inquiry model intgrated with PhET media valid to excercise science process skills of Junior High School Student. The learning materials development model used is Research & Development (R&D) with ten steps are related. Learning materials that developed was validated by experts and try out II toward 30 students of VII grade students on academic year 2016/2017 by using One Group Pre-test and Post Test Design. The results of this research : 1) The validity of the materials is very valid category; 2) the realization of the lesson plan categorized very good with percentage 98%, students response towards the learning material, 3) student activities highest in the activity of doing experiments and perform tasks LKS, 4) implementation learning reaches over 80% categorized as very strong; and 5) the increase in science process skills with N-gain 0.80, high criteria. It was concluded that learning material of science bases on guided inquiry model intgrated with PhET media that developed is eligible for increasing Junior High School students science process skills.